Anaerobic co-digestion of cyanide containing cassava pulp with pig manure. (August 2016) - Glanpracha, Naraporn; Annachhatre, Ajit P.
Highlights: Cyanide containing CP is a major by product from cassava starch industries. Co-digestion of cyanide-containing CP and PM was investigated. Digester sludge acclimatized well to cyanide in CP leading to cyanide degradation. Digester performance was stable between OLR of 2–6 kgVS/m 3  d. Particulate solubilization did not take place efficiently over OLR of 7 kgVS/m 3  d. Abstract: Anaerobic co-digestion of cyanide-containing cassava pulp with pig manure was evaluated using laboratory scale mesophilic digester. The digester was operated in a semi-continuous mode with the mixed feedstock having C/N ratio of 35:1. Digester startup was accomplished in 60 days with loading of 0.5–1 kgVS/m 3  d. Subsequently, the loading to digester was increased step-wise from 2 to 9 kgVS/m 3  d. Digester performance was stable at loading between 2 and 6 kgVS/m 3  d with an average volatile solid removal and methane yield of 82% and 0.38 m 3 /kgVSadded, respectively. However, beyond loading of 7 kgVS/m 3  d, solubilization of particulate matter did not take place efficiently. Cyanide present in cassava pulp was successfully degraded indicating that anaerobic sludge in the digester was well acclimatized to cyanide. The results show that cassava pulp can be successfully digested anaerobically with pig manure as co-substrate without any inhibitory effect of cyanide present in the cassava pulp.